Relationships Between Undergraduate Student Performance, Engagement, and Attendance in an Online Environment - Jones, Thomas J. (Frontiers in Education, 2022)
Monitoring student attendance and engagement is common practice during undergraduate courses at university. Attendance data typically show a strong positive relationship with student performance and regular monitoring is an important tool to identify students who may require additional academic provisions, wellbeing support and pastoral care, for example. However, most of the previous studies and our framework for monitoring attendance and engagement is based on traditional on-campus, in-person delivery. Accelerated by the COVID-19 pandemic, our transition to online teaching delivery requires us to re-evaluate what constitutes attendance and engagement in a purely online setting and what are the most accurate ways of monitoring. Here, I show how statistics derived from student interaction with a virtual learning environment, Canvas, can be used as a monitoring tool. I show how basic statistics such as the number and frequency of page views are not adequate and do not correlate with student performance. A more in-depth analysis of video viewing duration rather than simple page clicks/views is required, and weakly correlates with student performance. Lastly, I provide a discussion of the potential pitfalls and advantages of collecting such data and provide a perspective of some of the associated challenges.